K základní problematice managementu - Buchta, Miroslav (Univerzita Pardubice, 2002)
In this paper the autor, based on research, experience and literature, makes some basic management theory knowledge more precise, particularly definition and structure. Also practical cases of management problems are given, as a starting point for management teaching.
Keywords: Management; řízení; metody řízení; problémy